Chinese Students’ Perceptions of Extramural English Learning Activities for Vocabulary Acquisition: A Case Study at a Private University in Bangkok - Wang, Yue; Chinokul, Sumalee (THAITESOL Journal, 2025)
This study investigates Chinese undergraduate students’ perceptions of Extramural English Learning Activities (EELA) for vocabulary acquisition at a private university in Bangkok. Using a sequential mixed-methods design, data were collected from 128 questionnaires and 13 interviews with undergraduate students. Results show that students preferred contextual and meaningful vocabulary learning methods over rote memorization. They commonly used strategies such as inferencing, dictionary use, note-taking, and encoding, especially during receptive EELA—such as watching videos and reading—while productive activities like writing, conversations, and gaming were perceived as more effective for vocabulary retention, particularly by students who believed in learning through real-life use. The study further explores how students’ beliefs about vocabulary learning interact with their EELA choices and strategy use. Metacognitive strategies, including self-initiation and selective attention, also played an important role, while rehearsal and activation strategies were used less often but still contributed to learning. Overall, students preferred contextual and meaningful learning over rote memorization, showing a strong tendency toward self-directed vocabulary development. In this study, the term “Extramural” refers to language learning activities occurring outside formal classroom settings, often informally and self-initiated. These findings highlight the value of integrating EELA and strategy-based instruction into formal curricula to enhance learner autonomy and vocabulary acquisition.